Study of Consumer Preferences in Regard to the Blonde Orange Cv. Washington Navel "Arancia Di Ribera PDO". Issue 7 (3rd October 2017) - Ingrassia, Marzia; Sgroi, Filippo; Tudisca, Salvatore; Chironi, Stefania
ABSTRACT: Consumers' attitude and preferences in regard to food ingredients, country of origin, social corporate responsibility toward the environment, and work conditions have changed over the last 10 years. Consumers are getting more educated and therefore more sensitive around cultivation practices in agriculture and food processing, which increases concerns in regard to production practices in agriculture. Several studies have been conducted on consumers' preferences about quality food, but not with regard to blonde oranges cv. Washington Navel cultivated in southern Italy. This quality fruit is a niche product that achieved the Protected Designation of Origin (PDO) certification for high organoleptic properties and fine taste. In this study, by a survey of 400 Italian consumers, we discovered preferences in regard to the cv. Washington Navel PDO ( Riberella ) attributes and revealed variables that may influence consumers' purchasing behavior. Cluster analysis, based on respondents' rates on 20 attributes, revealed preference segmentation. Freshness, taste, and origin were the most important attributes for consumers, following visual appearance and quality/price ratio. In responding to the demands of consumers for quality fresh fruit, information about quality standards and about the Riberella PDO is poor. Therefore, there may be potential to develop specific policies and marketing strategies to product the position in the international market.